ANALISIS USAHA PEMASARAN DALAM RANGKA MENINGKATKAN PENJUALAN (Kasus Pedagang Ikan Segar Di Pasar Kodim pekanbaru) - Arios "; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research was conducted at Traders of fresh fish in a market focused onkey Kodim informannya is Masrial. As for the problems in this research areformulated in the formulation of the problem is whether the marketing efforts toincrease sales of fresh fish (fish market traders case study kodim Soweto)? Thisresearch aims to pemasran efforts to find out who carried out fresh fish merchants(Masrial) in order to increase sales.This research uses Qualitative descriptive method using the theoryadvanced by some of the authors of the marketing programs in order to increasesales in this study, researchers used indicators of the product, the price ofDistribution/location as the measuring analysis of marketing efforts in rankaincrease sales (fresh fish trader's case in the market town of Pekanbaru kodim)The research method used is the method of field research with data collectiontechniques interviews and observations with Key Informant and the informantestablished based on Pemeriksaaan research and research carried out at thechecking of this research is through another source, namely by means ofcomparing the data observations and interviews with key informants andinformants. This includes documents pertaining to the marketing efforts used bymerchants in fresh fish at the market of kodim pekanbaru.Keywords: Marketing, Sales, Trades